Інформаційні технології в управлінні розвитком солідарного туризму: аналітичні підходи та економічне прогнозування - Koval, O. I. (Forestry Education and Science: Current Challenges and Development Prospects, 2024)
Solidarity tourism, which is aimed at interaction with local communities, requires effective management and forecasting of the impact on the socio-economic development of regions. Solidarity tourism is an innovative and important form of tourism aimed at supporting local communities and preserving cultural and natural heritage. This form of tourism is characterized by social responsibility and is aimed at establishing close ties between tourists and the local population, promoting mutual development and cooperation. Solidarity tourism contributes to the development of regions, protection of the environment and improvement of the quality of life of local residents. Management of solidarity tourism requires a comprehensive approach that takes into account both economic and social aspects of tourism development, however, information technologies are becoming increasingly important to achieve these goals. The use of information technologies provides an opportunity to optimize management processes, expand opportunities for market analysis and create economic forecasting models. In these theses, the potential possibilities of computer technologies, the implementation of new projects, the role of the computer in the management of the work flow, as well as the system of management information in the tourism enterprise from the subsystem: internal reporting, collection of external current information about the environment surrounding the company, data marketing research and information analysis data that contribute to the development of solidarity tourism in Ukraine. The most important achievement in the field of tourism is computerization, because information technology in the field of management, directly or indirectly, gives recommendations to managers of tourism companies that face difficulties in the application of computer technologies.